The Application of Natural Material-Based Ecoprint Techniques in Improving Students' Creativity in Fine Arts Learning at MTsN 1 Mataram - Yustika, Tesa; Munawarah, Pyo Apriliana; Rahmat, Mi'Rajus Subyan; Tarenaksa S, Babat Nufus (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to describe the application of natural material-based ecoprint techniques in improving students' creativity in fine arts learning at MTsN 1 Mataram. This study used a descriptive qualitative approach, with students who participated in fine arts learning as the research subjects. Data were collected through observation, interviews, and documentation. The study was carried out through the stages of planning, preparation, implementation, and evaluation. During the learning process, students were introduced to ecoprint techniques and practiced them directly by using natural materials such as leaves and flowers as media for creating artworks.The results show that the application of natural material-based ecoprint techniques can improve students' creativity, as indicated by increased participation, exploration skills, as well as the diversity and originality of the artworks produced. In addition, this learning activity provided a contextual and enjoyable experience and fostered students' awareness of the importance of protecting the environment. Therefore, the ecoprint technique can serve as an innovative alternative in fine arts learning that focuses not only on the final product, but also on the creative process and the development of students' character